Laryngeal lipoma: case series- successful microlaryngeal surgery - Manohar, M. Babu; Rao, Soorya A. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Lipoma of the larynx is a very rare entity. In this study, we report two cases of lipoma of the larynx. The first case presented to us with hoarseness of voice and choking sensation and was diagnosed using a flexible fibreoptic video laryngoscopy and a computerised tomography (CT) of the neck. The lesion was excised surgically using microlaryngoscopic method. The diagnosis was confirmed histopathologically. Follow-up after 2 years showed no residual or recurrent lesions. The second case was a middle aged man with change in voice, burning sensation and foreign body sensation in throat. Flexible fibreoptic videolryngoscopy showed a small ventricular swelling on the right side in the anterior part. We considered the provisional diagnosis of a benign tumor and proceeded with microlaryngoscopic excision without any radiological investigation. Diagnosis of Lipoma was revealed after the histopathologic examination. We are reporting this case to highlight the rare location of the lesions and the successful use of microlaryngoscopic surgery.